2014
DOI: 10.3109/17483107.2014.968811
|View full text |Cite
|
Sign up to set email alerts
|

Living with an electric wheelchair – the user perspective

Abstract: PostprintThis is the accepted version of a paper published in Disability and Rehabilitation: Assistive Technology. This paper has been peer-reviewed but does not include the final publisher proof-corrections or journal pagination.Citation for the original published paper (version of record):Stenberg, G., Henje, C., Levi, R., Lindström, M. (2016) Living with an electric wheelchair: the user perspective. Disability and AbstractPurpose: To explore the experiences of using an electric wheelchair in daily livin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 40 publications
1
30
0
Order By: Relevance
“…According to Charmaz [13], people living with chronic diseases may limit their activity and autonomy rather than affirm further physical deterioration that would threaten their selfperception. The process of resistance and acceptance of using a wheelchair is thereby related to an on-going process of changing self-identity [12]. In this study, some of the young adults perceived that they were sometimes treated differently by people in society when they began to use a wheelchair, i.e., initially being viewed for "what" they are (a person with disability) rather than "who" they are (a unique person).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…According to Charmaz [13], people living with chronic diseases may limit their activity and autonomy rather than affirm further physical deterioration that would threaten their selfperception. The process of resistance and acceptance of using a wheelchair is thereby related to an on-going process of changing self-identity [12]. In this study, some of the young adults perceived that they were sometimes treated differently by people in society when they began to use a wheelchair, i.e., initially being viewed for "what" they are (a person with disability) rather than "who" they are (a unique person).…”
Section: Discussionmentioning
confidence: 84%
“…In this study, some of the young adults perceived that they were sometimes treated differently by people in society when they began to use a wheelchair, i.e., initially being viewed for "what" they are (a person with disability) rather than "who" they are (a unique person). Awareness of the varying reactions of others to the wheelchair and fear of not being regarded as the person they are has previously been described [12]. How a person is regarded by others involves both the self that a person intends to project through speech and actions, and also the self that others interpret from the person's speech and actions [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their contribution was an enhanced understanding of the driving difficulties that powered wheelchair users' experienced during daily activities including ecologically validated measurements for power wheelchair users, and identifying and refining the content of training programs specific to the use of power wheelchairs [10]. A recently published Swedish study showed that electric wheelchair users embodied their experiences of being a wheelchair user, and the wheelchair became much more than a device that helped them to mobility [11].…”
Section: Perspective Of the End Usermentioning
confidence: 99%